Reduction Of Anxiety In Parting Women With Intervention Hypnosis Five Finger In The Hospital Aura Syifa - Lingga Kusuma Wardani; Della Diva Nassyra (Journal of Health Science Community, 2024)
In labor often time Also arise flavor worried, panic And Afraid flavor Sick Which outside normal felt by the mother which can interfere with the labor process and result in prolonged labor birthing process. Anxiety in pregnant women if not handled seriously will has physical and psychological impacts and influences, both on the mother and the fetus. Study This use design study pre experimental design with type one groups pretest posttest . With technique purposive sampling obtained sample as much 28 respondent, variable independent hypnosis five finger to decline worry use scale zsas and the dependent variable is mother giving birth. The Wilcoxon statistical test was used. Research results from 28 It was found that most of the respondents felt moderate anxiety respondents with age 20-30 year as much 16 (57.1%) respondents. Whereas on Most of the births that experience anxiety are the first birth. Analysis use test statistics Wilcoxon obtained results “output “ test statistics” is known asymp. sig (2-tall) or mark p worth 0.001. Because mark 0.001 more small from <0.05, so it can be concluded that the "hypothesis is accepted" which means there is a decrease in anxiety Mother gave birth with five finger hypnosis intervention at Aura Syifa Hospital. Anxiety is not can only be treated with pharmacological therapy but can also be treated using non-pharmacological therapy, one of the interventions which is effective in alleviating worry is hypnosis five finger.